HAMBATAN DAN PROSPEK USAHA MIKRO KECIL KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Qomariah Lahamid; Julina Julina (Marwah: Jurnal Perempuan, Agama dan Jender, 2010)
This study aims to identify barriers and prospects for Small Micro Enterprises (SMEs) based on sex in the District of Singingi. The data collected by observation, interview and questionnaire. The result showed that the owners of SMEs in Singingi Regency dominated by men but not apart from the contribution of the woman (wife). The major obstacle is the lack of capital to develop the business. Other barriers such as availability of raw materials, equipment, technology, and skills possessed by SMEs. Although there are some obstacles, but they still want to maintain the business as their main motivation is to increase family income. Future prospects of SMEs will be better when it get serious attention from the government, especially when viewed from the economic growth rate reached 6 percent in that year provide the opportunity for absorption of industrial goods produced by SMEs.